Respostas

2013-10-28T20:07:21-02:00
2a/3 + b = 4  (mmc)                                                      x/2 - 3 = y
a      + 5 = 3b                                                                x        = y/2 + 3

2a +  3b =  12                                                              x -6 = 2y
  a   - 3b =   -5                                                              2x = y + 6 
3a          =   7
                                                                                      x = (y+6) /2
a = 7/3

substituindo em 
a + 5 = 3b
7/3 + 5 = 3b
3b = (7+ 15) /3
b = 22/9